Return to sport matters-longer-term quality of life after ACL reconstruction in people with knee difficulties - Filbay, S; Ackerman, I; Russell, T; Crossley, K (John Wiley & Sons Ltd, 2016)
Many individuals experience long-term quality of life (QOL) impairment following anterior cruciate ligament reconstruction (ACLR). Factors contributing to poor QOL and psychological health >5 years after ACLR remain unclear. This study aimed to describe QOL and psychological health outcomes in people with knee difficulties (pain, symptoms, or functional limitations) 5-20 years following ACLR and identify factors explaining variability in these outcomes. Participants with knee difficulties 5-20 years following ACLR completed a battery of validated patient-reported outcomes [including the Knee injury and Osteoarthritis Outcome Score (KOOS), ACL-QOL, and the Assessment of QOL (AQoL-8D) instrument]. Multivariable linear regression was used to identify factors explaining variability in outcomes. One hundred sixty-two participants aged 38 ± 9 (mean ± SD) years completed questionnaires 9 ± 4 (range 5-20) years following ACLR. Thirty-nine percent of participants returned to competitive sport, 28% returned to a lower level, and 32% did not return to sport after ACLR. Not returning to sport after ACLR was associated with worse KOOS-QOL (β = 0.29, P = 0.001 [mean ± SD (55 ± 20)], ACL-QOL [β = 0.48, P < 0.001; (57 ± 21)], and AQoL-8D [β = 0.22, P = 0.02 (0.80 ± 0.14)]) scores. Increased body mass index (56% were overweight/obese) was related to worse QOL and more depressive symptoms. Subsequent knee surgery and contralateral ACLR were also associated with poorer QOL outcomes in these individuals.